The impact of Facebook on libraries and librarians: a review of the literature. Issue 3 (1st July 2014) - Vassilakaki, Evgenia; Garoufallou, Emmanouel
Abstract : Purpose: – Social networking sites are becoming more and more popular triggering an increase in published research and impacting different aspects of daily life. One such aspect concerns libraries and librarians and the way they have adopted social networking sites. The purpose of this paper is to present a selective review on libraries' adoption and use of a specific social networking site such as Facebook in order to promote their services. Design/methodology/approach: – The method of selective review is employed to identify, document and present the relevant literature in a structured and annotated way. More specifically, all types of documents published between 2006 and 2012 are considered. In addition, the papers are assigned based on their expressed aim/s to emerged themes and sub-themes. Findings: – It was found that the main body of the reported literature focused on reporting experiences, problems and lessons learned from building a presence on Facebook. A few studies aimed to explore users' and librarians' perspectives towards social networking sites whereas there is a strong need for specific guidelines to assist libraries and librarians in adopting Facebook. Research limitations/implications: – This systematic literature review consists of articles published between 2006 and 2012. Originality/value: – This paper contributes to identifying, collecting and presenting research regarding the use of Facebook in the field of library science. In addition, it identifies and summarises the main problems and challenges libraries and librarians are faced with when employing Facebook.